2018
DOI: 10.1111/liv.13661
|View full text |Cite
|
Sign up to set email alerts
|

Liver zonation in children with non‐alcoholic fatty liver disease: Associations with dietary fructose and uric acid concentrations

Abstract: High fructose consumption is associated with disease severity in both lobular zones and hyperuricaemia may be associated with more severe disease in the periportal zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
1
14
0
2
Order By: Relevance
“…In line with recent cross-sectional studies in adults (145, 146), Vos et al (147) examined the relationship between SUA levels and NAFLD in the pediatric population, reporting that uric acid was significantly increased in those children with histological diagnosis of NASH compared with milder forms of NAFLD. In accordance with the latest study, Nobili et al (148) have recently observed that hyperuricemia, coupled with elevated dietary fructose consumption, could be responsible for the different pattern of lobular disease observed in pediatric NAFLD, determining greater damage in the periportal zone rather than in perivenous zone (148). Similarly, in a pilot study by Sullivan et al (149) children with NAFLD after fructose ingestion reported an exacerbated metabolic profile characterized by elevated serum glucose, insulin, and uric acid associated with an higher urinary levels of uric acid and a lower fructose excretion than lean subjects.…”
Section: Common Pathogenetic Mechanisms Linking Nafld and Metssupporting
confidence: 73%
“…In line with recent cross-sectional studies in adults (145, 146), Vos et al (147) examined the relationship between SUA levels and NAFLD in the pediatric population, reporting that uric acid was significantly increased in those children with histological diagnosis of NASH compared with milder forms of NAFLD. In accordance with the latest study, Nobili et al (148) have recently observed that hyperuricemia, coupled with elevated dietary fructose consumption, could be responsible for the different pattern of lobular disease observed in pediatric NAFLD, determining greater damage in the periportal zone rather than in perivenous zone (148). Similarly, in a pilot study by Sullivan et al (149) children with NAFLD after fructose ingestion reported an exacerbated metabolic profile characterized by elevated serum glucose, insulin, and uric acid associated with an higher urinary levels of uric acid and a lower fructose excretion than lean subjects.…”
Section: Common Pathogenetic Mechanisms Linking Nafld and Metssupporting
confidence: 73%
“…Chronic fructose ingestion, most notably in industrialized countries, has contributed to increasing prevalence of obesity and a myriad of chronic health conditions, including those involved with metabolic syndrome,7,13,14 that have produced a substantial economic and medical burden on our healthcare system 13,15. In particular, the hepatic consequences of metabolic syndrome have led to negative outcomes and continue to be a subject matter of interest 6,16,17…”
Section: Fructose In Diet and Healthcare Burdenmentioning
confidence: 99%
“…This is supported by the finding of increased steatosis in the portal area in rats fed with both sucrose and fructose‐enriched diets . Similarly, Nobili et al recently showed that high‐fructose intake in children correlated with increased portal steatosis, inflammation and hypothesis …”
Section: Paediatric Nafldmentioning
confidence: 72%